Motivasi Mempercayai Diri pada Lirik Lagu “Evaluasi” dan “Up&Up” Karya Hindia & Coldplay - Fakhri Fadhila Kamal; Firmansyah (UNISBA Press, 2024)
Abstract. Songs must actually be an effective means of conveying messages. This research aims to find out how the markers and signs of the motivational message of self-confidence in the lyrics of Coldplay's song